Bankruptcy Analysis Using Altmat Z-Score Method At Mining Company Pt Adaro Tbk 2015-2021 - Ayu, AYU RAHMAWATI (BISMA : Business and Management Journal, 2023)
This study aims to determine how big the potential for bankruptcy at the coal mining company PT. Adaro Tbk which has been listed on the Indonesia Stock Exchange is measured using one of the bankruptcy methods, namely the Altman Z-score method. The results of the analysis of this study are the results of all financial statements taken from the balance sheet and income statement of PT. Adaro Tbk in 2015-2021. The analytical technique used is the Altman Z-Score discriminant technique. The results obtained during the 7 year period that have been examined at PT. Adaro Tbk shows that this company is in a healthy condition because the index value of the company from the Z-score results shows a number above 2.60 which means it is not bankrupt and shows the highest value in 2017 with a value of 6.93 and the lowest value in 2020 with index value of 3.80.